Unilateral Pulmonary Artery Aplasia in a Pregnant Patient - Chitra Lal; Jim Barker; Charlie Strange (Case Reports in Medicine)
Unilateral pulmonary artery aplasia is a rare anomaly. Case reports of this condition in pregnant patients are even more uncommon and the best approach to management of such patients is still unclear. We report a patient who presented with a history of dyspnea, chest pain, and hemoptysis. Imaging established the diagnosis in a newly pregnant female. Management of the pulmonary artery aplasia patient in pregnancy requires prospective evaluation of pulmonary hypertension.